The Attitudinal Bridge: How Consumption Values Translate into Purchase Intentions for Viral Halal Food - Hanefar, Shamsiah Banu Mohamad; Osman, Ismah; Mohammad, Suleiman Ibrahim Shlash; Basir, Faziatul Amillia Mohamad; Vasudevan, Asokan; Ozturk, Ilknur; Fansuree, Mohd Ehsan; Rinaldi, Muammar (International Review of Management and Marketing, 2026)
In recent years, viral halal food trends driven by social media have gained increasing popularity among consumers. This study examines the multidimensional factors influencing consumers’ purchase intentions toward viral halal food. Drawing on the Theory of Consumption Values, the research investigates the effects of emotional value, epistemic value, and health concerns on purchase intention, with attitude serving as a mediating variable. A quantitative research design was employed using data collected from 241 respondents across diverse demographic groups in Malaysia. Data were analysed using SmartPLS through measurement and structural model assessment, including bootstrapping procedures. The findings indicate that emotional value and health concerns significantly influence both consumer attitude and purchase intention toward viral halal food. Attitude also significantly mediates the relationship between health concerns and purchase intention, suggesting that health-related values need to be internalised into favourable attitudes before driving behavioural intention. In contrast, emotional and epistemic values exhibit direct effects on intention without substantial mediation through attitude. These findings offer strategic implications for Malaysian MSMEs, food marketers, and public health advocates by highlighting that while virality may attract initial consumer interest, sustained participation depends on positive consumer evaluations of value, health, and trust. The study also supports United Nations SDG 12 Target 12.8 by promoting informed consumer choices and sustainable consumption behaviour.